2003
DOI: 10.1196/annals.1300.016
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and Depression

Abstract: The past decade has seen a steady accumulation of evidence supporting a role for the excitatory amino acid (EAA) neurotransmitter, glutamate, and its receptors in depression and antidepressant activity. To date, evidence has emerged indicating that N-methyl-d-aspartate (NMDA) receptor antagonists, group I metabotropic glutamate receptor (mGluR1 and mGluR5) antagonists, as well as positive modulators of alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors have antidepressant-like activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(78 citation statements)
references
References 173 publications
(176 reference statements)
4
70
0
Order By: Relevance
“…Additionally, the decrease of glutamate release by lamotrigine might be result of the blockade of pre-synaptic voltage-dependent sodium and calcium channels [46]. Our results corroborate previous experiments, demonstrating the involvement of NMDA receptors in the pathophysiology of depression [26,63]. We showed that anti-depressant like effect of lamotrigine was boosted by using different types of NMDA receptor antagonists, supporting the implication of NMDA in antidepressant-like effect of lamotrigine.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, the decrease of glutamate release by lamotrigine might be result of the blockade of pre-synaptic voltage-dependent sodium and calcium channels [46]. Our results corroborate previous experiments, demonstrating the involvement of NMDA receptors in the pathophysiology of depression [26,63]. We showed that anti-depressant like effect of lamotrigine was boosted by using different types of NMDA receptor antagonists, supporting the implication of NMDA in antidepressant-like effect of lamotrigine.…”
Section: Discussionsupporting
confidence: 94%
“…For example, blockade of NMDA receptors exerts antidepressant-like response [72]. Similarly, antidepressant agents diminish the function, activation, binding capacity and expression of NMDA receptors [11,62,63]. Surprisingly, only a small number of experiments reported the interaction of lamotrigine with NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of excitatory amino acid transmission may play a role in the etiology and pathophysiology of depression [121]. In clinical studies, it has been reported that elevated glutamate levels were observed in plasma and cerebrospinal fluid of depressed patients [4,87,98], and the administration of antidepressants has been shown to decrease plasma glutamate levels significantly in patients diagnosed with depression [89].…”
Section: Glutamatementioning
confidence: 99%
“…The NMDA system also plays a major role in mood regulation, specifically modulating depression and anxiety. 43,44 When activated by glutamate, NMDA receptors located on serotonin neurons exact distinct "anti-serotonin" effects and inhibite serotonin synthesis and release and increase serotonin degradation. All of these factors contribute to depression and anxiety.…”
Section: Nmdamentioning
confidence: 99%
“…43,44 Lamotrignine (Lamictal) decreases brain glutamate production, which decreases neuronal excitability, and is approved for the management of bipolar disorder and seizure disorders. 12 In an animal model, lamotrignine demonstrated a potent anxyolytic effect by decreasing the subjects' brain glutamate.…”
Section: Glutamatementioning
confidence: 99%